Revitalization of Developing Countries' Economy Through Islamic Finance - Ayu Annisa Fikra; Isnaini Harahap; Windu Anggara (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Islamic finance is a financial system based on sharia principles, such as the prohibition of usury, gharar, and maysir, which emphasizes justice, financial inclusion, and sustainability. This study aims to analyze the role of Islamic finance in the revitalization of developing countries' economies, focusing on instruments such as sukuk, zakat, waqf, and microfinance. Through the literature study method, this study shows that Islamic finance is able to support infrastructure development, community empowerment, and reduction of social inequality. This study analyzes the role of Islamic finance in the revitalization of developing countries' economies through instruments such as sukuk, zakat, waqf, and microfinance. The results of the study show that Islamic finance is effective in supporting infrastructure development, community empowerment, and reduction of social inequality in countries such as Indonesia, Malaysia, and Pakistan. However, its implementation still faces challenges, such as low Islamic financial literacy and limited regulations. The conclusion of the study confirms that Islamic finance has the potential to drive inclusive and sustainable economic growth if supported by increased literacy, regulatory harmonization, and expanded access to Islamic financial products.